2006
DOI: 10.1079/joh2005324
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara canis infections in a pig model: immunological, haematological and blood biochemistry responses

Abstract: The immunological, haematological and enzymatic responses to the inoculation in pigs of 100,000 embryonated eggs of Toxocara canis were studied. Fifteen females were inoculated and three remained as controls. Haematological values were analysed from day 7 p.i. until day 126 p.i. In the inoculated group, white blood cells were raised on day 14 p.i. and eosinophil values on days 7, 14, 21, 35 and 49 p.i. showing significant differences compared with controls (P < 0.05). Absolute eosinophil counts (per ml) presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The study showed the presence of a group of bands over 250 kDa, a band of 100 kDa, other bands around 75 kDa, 50 kDa, 37 kDa, and a group of bands of LMW with a triplet between 37 kDa and 25 kDa, recognized at different levels by the IgM+G, the IgG1 and the IgM. The bands detected by us were in agreement with the results obtained in other studies by WB in different animals, experimentally inoculated with Toxocara EE (Morales et al 2002 ;Sarimehmetoglu et al 2002 ;Sommerfelt et al 2001Sommerfelt et al , 2006. It has previously been established that bands of LMW between 35 and 24 kDa seem to be more specific to the genus Toxocara compared with bands of middle and high molecular weight (50-200 kDa) detected in patients infected with T. canis (Magnaval et al 1991).…”
Section: Discussionsupporting
confidence: 91%
“…The study showed the presence of a group of bands over 250 kDa, a band of 100 kDa, other bands around 75 kDa, 50 kDa, 37 kDa, and a group of bands of LMW with a triplet between 37 kDa and 25 kDa, recognized at different levels by the IgM+G, the IgG1 and the IgM. The bands detected by us were in agreement with the results obtained in other studies by WB in different animals, experimentally inoculated with Toxocara EE (Morales et al 2002 ;Sarimehmetoglu et al 2002 ;Sommerfelt et al 2001Sommerfelt et al , 2006. It has previously been established that bands of LMW between 35 and 24 kDa seem to be more specific to the genus Toxocara compared with bands of middle and high molecular weight (50-200 kDa) detected in patients infected with T. canis (Magnaval et al 1991).…”
Section: Discussionsupporting
confidence: 91%
“…Parasitic infections, including intestinal colonization with H. diminuta may cause disturbances in hematological blood parameters and changes in plasma composition (Figure 1) [80,81,82]. …”
Section: Rat Tapeworm Hymenolepis Diminuta Rudolphi 1819mentioning
confidence: 99%
“…Parasitic infections may be associated with an increase in the number of monocytes, neutrophils, and eosinophilsare [81,82,83,84,85]. Numerous studies have shown that an increased number of eosinophils in the blood accompanies parasitic diseases and allergic reactions.…”
Section: Rat Tapeworm Hymenolepis Diminuta Rudolphi 1819mentioning
confidence: 99%
“…Pig eosinophils can be isolated using discontinuous Percoll gradient to separate the granulocyte fraction and by a negative magnetic activated cell separation with mouse anti-pig CD16 antibody (Masure et al, 2013). Several publications presented data related to eosinophils, especially in the context of parasitic infections with A. suum (Masure et al, 2013), Trichuris suis (Steenhard et al, 2007), and Toxocara canis (Sommerfelt et al, 2006).…”
Section: Basophils and Eosinophilsmentioning
confidence: 99%